Pengaruh Kinerja Keuangan Terhadap Dividend Payout Ratio Pada Perusahaan Manufaktur - Istikha Ruchitra Hayudirga Wasesa; Rina Br. Bukit Bukit (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this research is to analyze the effect of financial performance such as Profitability, Leverage and Liquidity as well as the control variables namely Firm Size, Firm Age and Growth on the Dividend Payout Ratio (studies of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021). This study has a total population of 171 companies. The sampling technique used was purposive sampling in order to obtain 45 companies to be studied. The type of data used is secondary data. The data analysis technique used is panel data regression analysis. The data obtained and collected is then processed using the Eviews12 application. The results showed that profitability had a significant positive effect on the dividend payout ratio. Leverage has no significant negative effect on the dividend payout ratio. Liquidity has no significant negative effect on the dividend payout ratio. Firm size has a significant negative effect on the dividend payout ratio resulting in a significance value of 0.0001 <0.05 with a t-statistic value of -4.033250. Firm age has no significant positive effect on the dividend payout ratio resulting in a significance value of 0.2275 > 0.05 with a t-statistic value of 1.549685. Growth has a significant negative effect on the dividend payout ratio which results in a significance value of 0.0115 <0.05 with a t-statistic value of -2.587665.